1998
DOI: 10.1152/ajpcell.1998.274.6.c1563
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of myosin light chain phosphorylation at Ser19 and Thr18/Ser19in smooth muscle cells in culture

Abstract: Using the specific antibodies pLC1 and pLC2 for mono- and diphosphorylated 20-kDa myosin light chain (MLC20) at Ser19 and at both Thr18 and Ser19, respectively, we visualized the dynamics of the MLC20phosphorylation in rabbit aortic smooth muscle cells (cell line SM-3) stimulated with PGF2α. In the resting state, the diphosphorylated form was located in the peripheral region of the cell, such as the leading edge or the adhesion plaque, and the monophosphorylated form was located not only in the peripheral regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 37 publications
7
90
1
Order By: Relevance
“…For the comparison of LC 20 phosphorylation levels, cells were costained with a monoclonal (mouse) antibody (1:500) specific for phosphorylation of LC 20 at the MLCK sites, which was a gift from Drs. Y. Sasaki and M. Seto (Asahi Chemical Industry Co., Fuji, Japan) and has been previously characterized (31) and with rhodamine phalloidin (1: 2000, Molecular Probes) to label actin. For data analysis, a region was identified containing a filament bundle, and fluorescence for both LC 20 phosphorylation and actin were quantitated and integrated, and the ratio of LC 20 phosphorylation fluorescence/actin fluorescence was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…For the comparison of LC 20 phosphorylation levels, cells were costained with a monoclonal (mouse) antibody (1:500) specific for phosphorylation of LC 20 at the MLCK sites, which was a gift from Drs. Y. Sasaki and M. Seto (Asahi Chemical Industry Co., Fuji, Japan) and has been previously characterized (31) and with rhodamine phalloidin (1: 2000, Molecular Probes) to label actin. For data analysis, a region was identified containing a filament bundle, and fluorescence for both LC 20 phosphorylation and actin were quantitated and integrated, and the ratio of LC 20 phosphorylation fluorescence/actin fluorescence was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-phosphorylated MLC antibodies elucidated distinct mechanisms between mono-and diphosphorylation of rabbit smooth muscle MLC at the MLCK phosphorylatable sites (24). Application of these antibodies to immunostaining microscopy of the ␤-cell revealed that both mono-and diphosphorylated forms of MLC were distributed in the cell, even under nonstimulated conditions.…”
Section: Fig 4 Subcellular Localization Of Mlck In Min6 Cells Lowimentioning
confidence: 99%
“…The dried preparations were then incubated in urea-sample buffer (containting 20 mM Trizma base, 10 mM DTT, 8M urea) for 8 hrs at 4°C. The extracts were subjected to glycerol-PAGE coupled with Western blot (Sakurada et al, 1998;Katayama et al, 2006). MLC20 was detected with anti-MLC20 antibody given by Dr. S. Yoshiyama of Gunma University and visualized with horseradish preoxidase-conjutated anti rabbit IgG (GE Healthcare UK, Buckinghamshire, UK) and enhanced chemiliminescence (ECL) Western blotting detection system (ECL+plus, GE Healthcare, UK).…”
Section: Mlc20 Phosphorylationmentioning
confidence: 99%